2005
DOI: 10.1111/j.1365-2699.2005.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevational gradients of species diversity, breeding system and floral traits of orchid species on Réunion Island

Abstract: Aim This research investigates changes in orchid species composition and diversity, plant breeding system and floral traits along an elevational gradient spanning 2300 m (200-2500 m).Location The study was conducted on Réunion Island (Mascarene Islands, Indian Ocean).Methods Data on the distribution of 135 orchid species from 35 genera were gathered from 121 localities situated between 200 and 2500 m a.s.l. For each locality, 500-m transects were walked and each orchid species was recorded. Measures of species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
99
2
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 39 publications
12
99
2
6
Order By: Relevance
“…The humpshaped relationship of orchid species richness with the elevational gradient as affected by microclimate variables has also been ascertained in studies conducted in Mexico [29] as well as in Himalayan regions of Nepal and Bhutan [9]. This pattern has been observed in other tropical vascular plants [6,29] including trees and other epiphytes. In the Philippines, however, ecological studies on orchids and other vascular plants remain to be scanty in the literature.…”
Section: Phytogeographical Distribution (P²)mentioning
confidence: 71%
See 3 more Smart Citations
“…The humpshaped relationship of orchid species richness with the elevational gradient as affected by microclimate variables has also been ascertained in studies conducted in Mexico [29] as well as in Himalayan regions of Nepal and Bhutan [9]. This pattern has been observed in other tropical vascular plants [6,29] including trees and other epiphytes. In the Philippines, however, ecological studies on orchids and other vascular plants remain to be scanty in the literature.…”
Section: Phytogeographical Distribution (P²)mentioning
confidence: 71%
“…The different vegetation types may also explain the high levels of endemism. It was observed that some orchid species thriving at the very high elevation are isolated, habitatdependent and may become more specialized than those species found at lower elevation [22,6]. Eight endemic species present a new record in Bukidnon province, these include C. davaensis, Ceratostylis ramosa, Dendrobium diffusum, Dendrochilum coccineum, D. mindanaense, D. malindangense, Octarrhena parvula and Phreatia densiflora.…”
Section: Phytogeographical Distribution (P²)mentioning
confidence: 99%
See 2 more Smart Citations
“…), the spur nectar arises as an outgrowth from the proximal part of the labellum [9]. Beclardia macrostachya exhibit typical sphingophilous syndrome with white, spurred flowers and producing a strong scent [10,11]. Nevertheless, it has also been reported that grey white eye (Zosterops olivaceus) and olive white eye (Z. borbonicus) are the most probable pollinators of Beclardia macrostachya in Reunion Island [12].…”
Section: Introductionmentioning
confidence: 99%